The Relevance of Qur’anic-Based Learning in Enhancing Ethics in Vocational Technical Education: A Thematic Analysis of the Concept of Al-Ba?ar in the Qur’an - Pratiwi, Anggie; Bey, Safitriana; Nashihin, Indat (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study explores the relevance of the Qur’anic concept of al-Ba?ar, which encompasses moral and cognitive functions beyond sensory vision, as a reflective pedagogical framework in vocational technical education. Addressing a gap in prior research that rarely operationalizes specific Qur’anic concepts for vocational contexts, this study employs a library research design using a thematic interpretation (tafsir maudhu’i) approach. Data were drawn from selected Qur’anic verses containing the concept of al-Ba?ar, analyzed through classical and contemporary exegesis, and synthesized with educational ethics literature. The findings reveal that al-Ba?ar functions as an integrated perceptual system activated by zikr, enabling value-based technical decision-making. This conceptual integration offers a novel Qur’anic-based learning model to cultivate ethically grounded, socially responsive, and spiritually conscious vocational competencies. Penelitian ini mengkaji relevansi konsep al-Ba?ar dalam Al-Qur’an, yang mencakup fungsi moral dan kognitif melampaui penglihatan inderawi, sebagai kerangka pedagogi reflektif dalam pendidikan teknik vokasional. Menjawab kesenjangan penelitian terdahulu yang jarang mengoperasionalkan konsep Qur’ani secara spesifik untuk konteks vokasional, kajian ini menggunakan metode studi pustaka dengan pendekatan tafsir tematik (tafsir maudhu’i). Data diambil dari ayat-ayat terpilih yang mengandung konsep al-Ba?ar, dianalisis melalui tafsir klasik dan kontemporer, serta disintesiskan dengan literatur etika pendidikan. Hasil penelitian menunjukkan bahwa al-Ba?ar berfungsi sebagai sistem persepsi terintegrasi yang diaktifkan oleh zikr, sehingga memungkinkan pengambilan keputusan teknis berbasis nilai. Integrasi konseptual ini menawarkan model pembelajaran berbasis Qur’ani yang baru untuk membentuk kompetensi vokasional yang etis, tanggap sosial, dan sadar spiritual.